2011
DOI: 10.1111/j.1365-2842.2011.02239.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of cognitive‐behavioural therapy for temporomandibular disorders: a systematic review

Abstract: Cognitive-behavioural therapy (CBT) and its effects on temporomandibular disorders (TMD) have been examined in several studies. We are trying to combine results of these studies and to explore the effectiveness. MEDLINE, EMBASE, Cochrane Central Register of Controlled Trial, Pubmed and the Chinese Biomedical Literature Data were searched to collect randomised and semi-randomised controlled trials (RCTs), comparing CBT with any control group receiving other dental treatments. Two authors independently retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 29 publications
0
19
0
4
Order By: Relevance
“…This statement was confirmed by Liu et al (9) in a systematic review about the effectiveness of the CBT for patients with TMD. Those authors could include only five studies with some methodological limitations and concluded that there is a clear and urgent need for well-designed randomized controlled trials examining CBT for TMD.…”
Section: Discussionmentioning
confidence: 59%
“…This statement was confirmed by Liu et al (9) in a systematic review about the effectiveness of the CBT for patients with TMD. Those authors could include only five studies with some methodological limitations and concluded that there is a clear and urgent need for well-designed randomized controlled trials examining CBT for TMD.…”
Section: Discussionmentioning
confidence: 59%
“…28 Acupuncture is of limited long-term benefit 23 29 30 and there is insufficient evidence to support the use of low level laser therapy. 31 32 There is currently some evidence for the effectiveness of cognitive behaviour therapy (CBT) 33 and physiotherapy. 34 35 A Cochrane systematic review found 11 poor-quality studies on pharmacological therapy and there is inconclusive evidence for analgesics, benzodiazepines, anticonvulsants, Facial pain diagnosis and management 36 An open-label study of amitriptyline showed some benefit 37 whereas no benefit was noted in an RCT of Botulinum Toxin.…”
Section: Temporomandibular Disorders (Tmd)mentioning
confidence: 99%
“…Likewise, several studies, including systematic reviews, revealed no strong evidence supporting the superiority of occlusal treatment over any other treatment modalities (e.g. cognitive behavioural, pharmacological or physical therapies) (30)(31)(32)(33)(34). In addition, altering the lateral occlusion schemes will not necessarily prevent or reduce the incidence of TMD.…”
Section: Tmd Relationshipmentioning
confidence: 99%